Treatment decisions for older adults with advanced chronic kidney disease - Steven J. Rosansky; Jane Schell; Joseph Shega; Jennifer Scherer; Laurie Jacobs; Cecile Couchoud; Deidra Crews; Matthew McNabney (BMC Nephrology, 2017)
Abstract Dialysis initiation rates among older adults, aged 75 years or greater, are increasing at a faster rate than for younger age groups. Older adults with advanced CKD (eGFR < 30 ml/min/1.73 m2) typically lose renal function slowly, often suffer from significant comorbidity and thus may die from associated comorbidities before they require dialysis. A patient’s pattern of renal function loss over time in relation to their underlying comorbidities can serve as a guide to the probability of a future dialysis requirement. Most who start dialysis, initiate treatment “early”, at an estimated glomerulofiltration rate (eGFR) >10 ml/min/1.73 m2 and many initiate dialysis in hospital, often in association with an episode of acute renal failure. In the US older adults start dialysis at a mean e GFR of 12.6 ml/min/1.73 m2 and 20.6% die within six months of dialysis initiation. In both the acute in hospital and outpatient settings, many older adults appear to be initiating dialysis for non-specific, non-life threatening symptoms and clinical contexts. Observational data suggests that dialysis does not provide a survival benefit for older adults with poor mobility and high levels of comorbidity. To optimize the care of this population, early and repeat shared decision making conversations by health care providers, patients, and their families should consider the risks, burdens, and benefits of dialysis versus conservative management, as well as the patient specific symptoms and clinical situations that could justify dialysis initiation. The potential advantages and disadvantages of dialysis therapy should be considered in conjunction with each patient’s unique goals and priorities. In conclusion, when considering the morbidity and quality of life impact associated with dialysis, many older adults may prefer to delay dialysis until there is a definitive indication or may opt for conservative management without dialysis. This approach can incorporate all CKD treatments other than dialysis, provide psychosocial and spiritual support and active symptom management and may also incorporate a palliative care approach with less medical monitoring of lab parameters and more focus on the use of drug therapies directed to relief of a patient’s symptoms.